PENGARUH MODEL PEMBELAJARAN COOPRTIVE LEARNING TIPE STUDENT TEMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG KELAS V SD N 01 NANGSRI KEBAKKRAMAAT TAHUN PEMBELAJARAN 2022/2023 - nadia putri; sugiaryo sugiaryo; sarafuddin sarafuddin (UNIVERSITAS SLAMET RIYADI, 2023)
This study aims to determine the effect of the existence of the STAD learning model on the results of learning mathematics in class V SD Negeri 01 Nangsri Kebakkramat. This type of research uses quantitative research using the Pre-Experimental Experiment method in the form of one-group pretest posttest. Using a population and a sample of 25 people. Instrument testing was carried out with 25 multiple choice questions. The data analysis technique was in the form of a prerequisite test as an initial stage of analysis using the Kolmogorof Smirnov formula and the hypothesis test used was the Paired Sample T-Test. Based on the results of the Paired Sample T-Test, the value was 18.004, then compared with df (N-1) so it was 25-1 = 24 at a 5% significance level, namely 2.063. So (18.004) > (2.063) which means H_o is rejected H_a is accepted. So the hypothesis states that there is an effect of the STAD learning model on mathematics learning outcomes in the material for class V SD Negeri 01 Nangsri Kebakkramat Academic Year 2022/2023 is accepted as true. Keywords: STAD Learning Model, Mathematics, Building Space.